THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN IMPROVING EMPLOYEE PERFORMANCE WITH THE DESIRE TO ACHIEVE AS A MEDIATION VARIABLE AT PT GRACIA KREASI ROTAN UNIT 1 CIREBON - Anna Suzana; Dina Luthfiyah Nurjanah (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the effect of transformational leadership on employee performance with achievement motivation as a mediating variable at PT Gracia Kreasi Rotan Unit 1 Cirebon. The research approach used is quantitative with a causal associative design. Data were collected through questionnaires distributed to production employees and analyzed using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The results of the study indicate that transformational leadership has a positive and significant effect on employee performance. In addition, transformational leadership has also been shown to have a positive effect on employee achievement motivation. Achievement motivation, in turn, has a positive and significant effect on employee performance. Other findings reveal that achievement motivation plays a significant mediating variable in the relationship between transformational leadership and employee performance. These findings indicate that employee performance improvement is not only determined by leadership style, but also by employees' internal drive to achieve. This study provides practical implications for company management in designing transformational leadership strategies that are able to foster achievement motivation so that employee performance can improve sustainably.